Continuous Positive Airway Pressure or Humidified High Flow Nasal Cannula for Respiratory Distress Syndrome: A Randomized Control Trial among Premature Neonates - Tahereh Esmaeilnia Shirvani; Fatemeh Sadat Nayeri; Mamak Shariat; Nikoo Niknafs; Mohamad Reza Mirjalili; Seyyed Nasrollah Hosseini; Vafa Ghorbansabagh (Mashhad University of Medical Sciences, 2020)
Background: Respiratory distress syndrome (RDS) is a common lung problem in neonates born before 28 weeks of pregnancy. The current study aimed to assess the clinical outcomes of Nasal Continuous Positive Airway Pressure (NCPAP), as compared to humidified high flow nasal cannula (HHFNC) in the treatment of premature neonates with RDS.Methods: This randomized control trial was conducted on 60 preterm neonates (gestation Results: There were no significant differences in primary and secondary outcomes, including pneumothorax, patent ductus arteriosus (PDA), chronic lung disease, surfactant injection, tracheal intubation, death, necrotizing enterocolitis (NEC), days of delay in establishing full enteral feeds, duration of hospitalization, and the number of the days for oxygen requirement between NCPAP and HHFNC groups.Conclusion: HHFNC and NCPAP techniques have the same efficacy in the treatment of RDS in neonates, and there was no difference between the two techniques in terms of treatment failure and clinical outcomes. Since HHFNC is less invasive with the same efficacy compared to CPAP, we recommend that it can be used as a primary modality in preterm neonates with RDS.